Financial subsidies, female employment, and plant performance — Evidence from a quasi-experiment - García, Raffi E.; López Rago, Ricardo A. (Journal of Financial Stability, 2025)
This paper exploits changes in financial subsidy programs to investigate their effect on female employment and firm performance. The identification strategy uses a quasi-experiment from a government policy change that eliminated financial support for exporting plants in the Chilean manufacturing industry. The difference-in-differences methodology shows that the policy change increased the share of total female employment by 3.3%, driven mainly by an increase of female workers in blue-collar occupations. In comparison, male labor experienced a drop of 4.4% in white-collar occupations in the treated plants relative to those in the control group. Plant total factor productivity (TFP) decreased due to the policy change, but both total gross output and sales rose approximately 7% on average. The paper explores two possible mechanisms to explain these findings: the technology adoption channel and changes in the gender composition of labor in the presence of a gender pay gap. The findings are consistent with the international trade and corporate finance literature on firm behavior under high market fixed and sunk costs.